Effect of gamma irradiation on physicochemical, structural and rheological properties of plant exudate gums. (December 2017) - Hamdani, Afshan Mumtaz; Wani, Idrees Ahmed; Gani, Adil; Bhat, Naseer Ahmad; Masoodi, Farooq Ahmad
Abstract: This study was undertaken to determine the effect of gamma irradiation on physicochemical characteristics of acacia, apricot and karaya gum. The moisture and carbohydrate content varied significantly ( p ≤ 0.05) from 8.83–11.12 and 77.98–83.08 g/100 g, respectively, in native gums. Protein, fat and ash content also varied significantly among the gums (1.63–2.25, 0.09–1.10 and 3.67–5.72 g/100 g, respectively). Functional properties like water absorption, emulsifying, swelling and solubility index increased with the increase in irradiation dose (0–5 kGy). Viscosity of the aqueous gum dispersions measured using RVA decreased with irradiation under natural and acidic environments. Absorbance of the functional groups like –OH, –COOH, uronic acid and pyranose units increased upon irradiation in acacia and karaya gum as confirmed by FT-IR analysis. Irradiation had a pronounced effect on the rheology of acacia and apricot gums reducing their viscosity. In case of karaya gum, there was a transaction of gel-like solid behaviour to viscous liquid behaviour upon irradiation. Graphical abstract: Highlights: Irradiation upto 0–5 kGy increased the water absorption capacity of gums. Irradiation and decrease in pH reduced the viscosity of gums. The gel formation tendency was highest in karaya gum. Irradiation caused the changes at structural level of gums.